Green Finance in Indonesia's Low Carbon Sustainable Development - Setiawan, Sigit; Ismalina, Poppy; Nurhidajat, R; Tjahjaprijadi, Cornelius; Munandar, Yusuf (International Journal of Energy Economics and Policy, 2021)
This paper primarily discusses how Indonesia - as a developing country and one of the world's top 10 greenhouse gas (GHG) contributors – has committed and struggled to attain low carbon development goals, which are crucial for its national development sustainability and the world campaign on climate change impact mitigation and adaptation. Indonesia's awareness of the impact of disasters due to climate change on the sustainability of its national development brings forth commitments at the international level and robust programs at the national level in reducing GHG emissions. These programs have delivered historical achievements, especially in the forestry sector and the energy sector, the two most critical sectors of national GHG emission. Discussions continue on the conceivable green finance support options varying from the banking sector until the facilitation of ASEAN regional cooperation on low carbon sustainable development. The awareness of stakeholders to prevent potentially excessive burdens on Indonesian public green finance has delivered continuing responses to stimulate private green finance to contribute more for low carbon sustainable development. The study concludes with the exploration of current challenges to address in order to boost the Indonesian dominant banking sector contribution up to the next level. Keywords: climate change, forestry, energy, public finance, private finance, ASEAN regional cooperation JEL Classifications: O13, O19, O23, O38, G21 DOI: https://doi.org/10.32479/ijeep.11447